Model Pengembangan Kurikulum Riset Konstruktif-Integratif dalam Meningkatkan Prestasi Akademik di MAN 2 Tulungagung - Hawwin Muzakki (Southeast Asian Journal of Islamic Education Management, 2024)
This research highlights significant differences between research approaches at State Islamic Senior High School (MAN) and University curricula. The research curriculum development, adjustment, and modification at the madrasah level are the main attractions for researchers who want to continue their research and in-depth study of the research curriculum at MAN 2 Tulungagung. This research seeks to explore the curriculum development model at MAN 2 Tulungagung to explain the research curriculum development at MAN 2 Tulungagung by borrowing Tyler's curriculum development theory. This research was explored using in-depth interviews, documentation and participant observation. The approach used in this study is qualitative. The data obtained was analyzed using the stages of data collection, presentation, condensation, and conclusion. This research concludes the research curriculum development model at MAN 2 Tulungagung using a constructivist-integrative model with the steps: (1) Using a clear legal basis, (2) Integrating the independent curriculum and research curriculum, (3) Carrying out a preliminary study, (4) ) Designing intracurricular, extracurricular and incidental development activities, (5) Developing research curriculum components, (6) Organizing the curriculum, (7) Collaborating with other agencies, and (8) Evaluating research programs which are carried out sequentially and continuously.